Structure, histochemistry and seasonal variations of the male reproductive accessory glands in the Pallas - Christante, Caroline Maria [UNESP]; Beguelini, Mateus Rodrigues [UNESP]; Puga, Cintia Cristina Isicawa [UNESP]; Negrin, Ana Carolina [UNESP]; Versute, Eliana Morielle [UNESP]; Vilamaior, Patricia Simone Leite [UNESP]; Taboga, Sebastião Roberto [UNESP] (CSIRO Publishing, 2013)
Due to their wide geographical distribution, bats suffer considerable influence from abiotic factors on their reproductive strategies, detected through behavioural or functional assessment of the gonads and accessory glands. The present study aimed to characterise anatomically and morphologically the reproductive accessory glands (RAGs) of Molossus molossus (Molossidae) and evaluate their seasonal variations. The RAGs were removed, fixed, sectioned after histological processing and submitted to the following stains: haematoxylin–eosin, periodic acid–Schiff (PAS) and Go¨mo¨ri’s reticulin. Our data demonstrated that the RAGs of M. molossus are composed of a semi-lobed prostatic complex associated with the urethra and a pair of inguinal bulbourethral glands. Histology and three-dimensional reconstruction of the prostatic complex demonstrated the existence of two regions: ventral and dorsal (named according to the position around the urethra). The two regions had distinctive morphological and histological differences, with the ventral region being the most prominent and the dorsal formed by four lobes. Considering the seasonal evaluation, we can infer that the prostatic complex of M. molossus is active throughout the seasons in Sa˜o Paulo State (Brazil) and, although each of the prostatic regions has inherent characteristics, they synchronise to establish the main reproductive peak in spring (early rainy season).
Keywords: Prostate; Sazonalidade; Molossus; Chiroptera; bat reproduction; prostate; reproductive peak; seasonality